2020
DOI: 10.1002/arch.21684
|View full text |Cite
|
Sign up to set email alerts
|

Plodia interpunctella (Lepidoptera: Pyralidae): Intoxication with essential oils isolated from Lippia turbinata (Griseb.) and analysis of neuropeptides and neuropeptide receptors, putative targets for pest control

Abstract: The Indian meal moth Plodia interpunctella is a pest of stored products worldwide. Plant-derived essential oils with insecticidal activity could be safe products to control this species. The scarce information about the mode of action of most plant-derived products limits their use for the control of insect pests. Here, we demonstrate that an essential oil distilled from Lippia turbinata ("poleo") has insecticidal activity on P. interpunctella larvae. Furthermore, we performed a comprehensive characterization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…The EO caused mortality in larvae in a dosedependent manner, with an LC 50 value of 432.9 mg/L. Furthermore, the EO caused a delay in the pupation day in the surviving larvae, which was correlated with a low expression of the neuropeptides responsible for regulating the postembryonic development in lepidopterans (Corzo et al, 2020).…”
Section: Insects That Affect Stored Grains and Food Commoditiesmentioning
confidence: 97%
See 1 more Smart Citation
“…The EO caused mortality in larvae in a dosedependent manner, with an LC 50 value of 432.9 mg/L. Furthermore, the EO caused a delay in the pupation day in the surviving larvae, which was correlated with a low expression of the neuropeptides responsible for regulating the postembryonic development in lepidopterans (Corzo et al, 2020).…”
Section: Insects That Affect Stored Grains and Food Commoditiesmentioning
confidence: 97%
“…The moth Plodia interpunctella is a major economic insect pest of stored products and processed food commodities found worldwide. Corzo et al (2020) evaluated the insecticidal activity of L. turbinata EO in P. interpunctella third-instar larvae. The EO caused mortality in larvae in a dosedependent manner, with an LC 50 value of 432.9 mg/L.…”
Section: Insects That Affect Stored Grains and Food Commoditiesmentioning
confidence: 99%
“…Corzo (2020) demonstrated that the essential oil from Lippia turbinata, known as "poleo," has been shown to have an insecticidal effect on P. interpunctella larvae [39]. In addition, they thoroughly characterized the neuroendocrine system of P. interpunctella in contrast to other lepidopteran species.…”
Section: Biochemical Controlmentioning
confidence: 99%
“…This formulation can increase the insecticidal efficacy of EO twofold [192]. The essential oil distilled from Lippia turbinata ("poleo") was insecticidal on P. interpunctella larvae [198]. In a recent study, the essential oils (O. vulgare, P. anisum and Tanacetum cinerariifolium) and four plant extracts (Agastache rugosa, Capsicum annuum, C. reticulata and Ginkgo biloba) were proven to be repellent against P. interpunctella.…”
Section: Butterflies and Moths (Lepidoptera)mentioning
confidence: 99%